From Drosophila to mammals: The evolutionarily conserved homeodomain protein Engrailed affects the antitumor innate immune response - Jieqing Huang; Xiao Lan; Xiaoming Huang; Yuntong Yuan; Mo Liu; Jiyong Liu; Juanjuan Chen; Zhenhui Ye; Ziming Wei; Yuqiang Chen; Zihao Deng; Yuhong Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
In the process of investigating innate immune reactions against injected oncogenic cells in Drosophila , we noted that the homeodomain protein Engrailed, known since last century for its role in segmentation polarity in embryos, is reactivated in adult males where it considerably restricts the expected proliferation of these cells. Importantly, this effect was not induced following injection of selected pathogens or primary Drosophila embryonic cells. We show that the injection of these cells induces the nuclear translocation of the cytosolic Engrailed protein, and we identify a series of downstream effector genes which are either positively or negatively regulated by this transcription factor. Our results point to unexpected functional parallels between engrailed genes in mammals and flies, which is further illustrated by the phenotypes induced in fly wings and tumor load after ectopic expression of mammalian genes in flies.